Heraldry : its origins and meaning - Pastoureau, Michel, 1947-; Garvie, Francisca (London : Thames and Hudson, 1997)
History of arms - The language of heraldry - A misunderstood science - The fleur-de-lis - The eagle and the lion -The right to bear arms - Heraldry in Britain - Visitations - Shakespeare's coat of arms - The suppression of 'sign of feudalism' - The Japonese mon -The words to say it
Includes bibliographical references (page 132) and index.
Translated from the French
Keywords: Heraldik; Heraldry -- History; Heraldry; History